2022
DOI: 10.1002/adhm.202200728
|View full text |Cite
|
Sign up to set email alerts
|

A Bioprinted Bruch's Membrane for Modeling Smoke‐Induced Retinal Pigment Epithelium Degeneration via Hybrid Membrane Printing Technology

Abstract: The retinal pigment epithelium (RPE) not only forms the outer blood-retinal barrier (oBRB) but also plays a multifunctional role in the ocular system. The loss of this epithelium leads to serious diseases resulting in vision impairment. No effective treatment is available for the repair of RPE damage. A functional in vitro RPE model that allows the recapitulation of oBRB-related pathophysiological responses is lacking. Here, a hybrid membrane printing technology is developed to fabricate cellular monolayers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, they utilized a 3% gelatin bioink to bioprint retinal pigment epithelial cells on the top layer, producing a single-cell layer. In vitro experiments have demonstrated that this organoid bioink-printed blood-retinal barrier model displays functions related to barrier clearance, vision, and maintenance [137] (figures 12(A)-(C)). In another study, Kapil Bharti successfully utilized bioprinting to create a natural, three-dimensional oBRB tissue.…”
Section: Retinamentioning
confidence: 99%
“…Subsequently, they utilized a 3% gelatin bioink to bioprint retinal pigment epithelial cells on the top layer, producing a single-cell layer. In vitro experiments have demonstrated that this organoid bioink-printed blood-retinal barrier model displays functions related to barrier clearance, vision, and maintenance [137] (figures 12(A)-(C)). In another study, Kapil Bharti successfully utilized bioprinting to create a natural, three-dimensional oBRB tissue.…”
Section: Retinamentioning
confidence: 99%
“…Three-dimensional bioprinted retinal tissue models can also be used to study external environmental factors on ocular health. Kim et al found that oxidative stress induced by cigarette smoke can disrupt RPE tight junction strength and blood–retinal barrier function [ 66 ]. This information can be used to further explore causative links between smoking and retinal degeneration.…”
Section: Retinal Applicationsmentioning
confidence: 99%
“…In vivo , transparency of the R5-CEC membranes was better maintained than acellular membranes, demonstrating that cell engineering and 3DP delivery of CECs led to better cell survival and function. Similarly, another group used 3DP to generate a multilayered structure consisting of a vitrified decellularized Bruch’s membrane (BM) layer with retinal pigment epithelial (RPE) cells encapsulated in a sacrificial gelatin layer on top . This structure functioned as a model of the outer blood–retinal barrier to assess the disease conditions on RPE cell function.…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…Similarly, another group used 3DP to generate a multilayered structure consisting of a vitrified decellularized Bruch's membrane (BM) layer with retinal pigment epithelial (RPE) cells encapsulated in a sacrificial gelatin layer on top. 110 This structure functioned as a model of the outer blood−retinal barrier to assess the disease conditions on RPE cell function. Bioprinting allowed functional monolayer formation of RPE cells on the basement membrane to accurately replicate native anatomy, and the effects of cigarette smoke extract on cell function were evaluated.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%